Didactic materials applied in English language teaching focused in the writing of the Supervised Internship Reports - Melo, Lívia Chaves (BELT - Brazilian English Language Teaching Journal, 2019)
Within the interdisciplinary field of Applied Linguistics, this research proposes analyzing how the Supervised Internship Reports that focus the use of didactic materials applied in the teaching and learning English language during the practicum activities help pre-serve teachers to reflect upon the teaching practice. Dialogical studies of language according to Bakhtin’s perspective is the theoretical apparatus that guided this research. Qualitative research approach and the methodology of documentation were applied to characterize supervised internship reports. The research results show that the use of didactic materials it is focused in the writing of the Supervised Internship reports, however, it is essential to invest in the adaptation and production of materials that attend the objectives and characteristics of the English language teaching contexts.